Identiteta ljudi z demenco - Penič, Benjamin (Socialno delo, 2022)
Human identity is dynamic, fleeting, and changeable and is formed in social contexts. People with dementia are considered a vulnerable group with a less stable identity due to the nature of the disease, often causing their individuality to be disregarded. Systematic review of the literature shows that the living and social environments play an important role in the consolidation, maintenance, and reconstruction of the identity of people with dementia. Interactions of people with dementia with their living and social environments enable them to learn new strategies for expressing their identity, while social capital remains a valuable source of power in the process of identity expression, consolidation, or reconstruction. The narratives of people with dementia contribute to the preservation of their personal identity and enable reviving memories. The opportunity to share experiences and participate in social interactions serves as recognition of their uniqueness and provides them a sense of worth and value. People with dementia want to participate and engage in activities, as many are an essential building block of their identity. Successful completion of activities also helps maintain a positive self-image and experience their own worth.
Keywords: bivalno okolje; dolgotrajna oskrba; living environment; long-term care; osebna identiteta; personal identity; social environment; social identity; social work; socialna identiteta; socialno delo; socialno okolje